Antitumor potential, anticancer property and phycochemical screening of Padina minor yamada extracts. - Subong, Bryan John Jereza (2011.)
The present study was conducted to evaluate the antitumor potential, anticancer property and phycochemical screening of Padina minor Yamada using different solvent extracts namely hexane, dichloromethane, ethyl acetate, methanol, and aqueous. The antitumor potential was performed using the brine shrimp lethality assay (BSLA). The anticancer activity made use of mechanism-base activity using mutant yeast strains namely 1138, 1140, and 1353 and the SC7 yeast strain bioassay. It was found out that the methanol extract, hexane and the ethyl acetate has LC50 at 48 hours which are closest to the standard set by the National Cancer Institute which is 30ppm. ANOVA revealed that the all extracts have no significant difference in terms of brine shrimp mortality at 48 hours compared to anticancer drugs Vinblastine and Etoposide. yeast bioassay revealed that the Hexane extract shows bioactivity on Topoisemerase I (yeast strain 1140) while the Ethyl acetate extract shows bioactivity on Topoisomerase II (yeast strain 1353). ANOVA revealed that the said two extracts have significant difference with the positive control Nystatin, antifungal agent, suggesting that the activity is other than antifungal. The Hexane, Ethyl Acetate, and Methanol extract has shown inhibition against Sc7 yeast strain. Results for the bioassay revealed that there is significant difference between the extracts inhibition activity as compared to the positive control, Nystatin. Phycochemical screening showed that the methanol extract has the msot number of compounds groups along with the ethyl acetate extract. The order of abundance of the metabolites in terms of mass is polar, medium-polar and non-polar metabolites, respectively.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Padina Minor; Yamada Extracts